Successful laparoscopic distal pancreatectomy for a large solid pseudopapillary neoplasm: A case report. Issue 3 (8th February 2017) - Tada, Seiichiro; Iida, Taku; Anazawa, Takayuki; Yagi, Shintaro; Seo, Satoru; Masui, Toshihiko; Kaido, Toshimi; Takaori, Kyoichi; Uemoto, Shinji
Abstract: A 30‐year‐old Japanese woman presented at our hospital with a pancreatic tumor. Contrast‐enhanced CT revealed a tumor with a 12‐cm diameter in the pancreatic body and tail. In the preoperative setting, endoscopic ultrasound‐guided fine‐needle aspiration permitted a histopathological diagnosis of solid pseudopapillary neoplasm. Twhe patient underwent laparoscopic distal pancreatectomy with splenectomy. Our procedure involved three steps. Firstly, the splenic artery was occluded to block inflow of blood to the tumor. Then, we transected the neck of the pancreas using radical antegrade modular pancreatosplenectomy. Finally, hand‐assisted laparoscopic surgery allowed us to secure the operating field and easily handle the large tumor. This enabled us to accomplish laparoscopic distal pancreatectomy, and en‐bloc resection was completed. The patient was discharged without major complications. Laparoscopic distal pancreatectomy for huge solid pancreatic tumors can be completed safely.